Modelo de Gestión Humana en empresa pyme: Mercopa S.A.S. - Osorio-Quintero, Carolina (My University, 2020)
El presente trabajo de grado tiene como objeto definir una propuesta del modelo de gestión humana en la empresa pyme: Mercado Copacabana S.A.S, mediante la aplicación de elementos estratégicos y organizacionales descritos y analizados en éste documento. Debido a la ausencia de una estrategia empresarial y a un proceso de gestión humana que estuviera alineado a los objetivos organizacionales, se vio la necesidad de diagnosticar, diseñar e implementar la planeación estratégica y el modelo de gestión humana que tendrá procesos sólidos para la optimización del desempeño de los colaboradores, que impactará finalmente los resultados de la Organización. El modelo de gestión humana que se definió para la empresa Mercado Copacabana S.A.S., fue creado mediante diversos modelos de gestión humana referenciados, acorde con las necesidades del sector y las expectativas de la Organización, obteniendo un modelo sólido y completo que sirva de ejemplo para empresas pymes en la actualidad. Implementar la planeación estratégica y el nuevo modelo de Gestión Humana no tiene ningún coste económico para la empresa, sin embargo, se deben realizar actividades de comunicación interna para que todos los cambios sean comprendidos e implementados por todo el personal, haciéndolos parte de la cultura de la Organización.
This project’s purpose is to present a proposal of the Human Resources Model in the Company, Mercado Copacabana S.A.S, through the application of strategic and organizational elements described and analyzed in this document. Due to the lack of a dedicated talent management department and a business strategy, it is necessary to analyze, design and implement strategic planning and human resources processes with the objective of improving the performance of employees and the organization’s results. This project offers a diagnostic of Mercopa S.A.S and a proposal, with the objective of creating or/and updating the organizational elements and the company's human resources model. The human resources model was defined with Mercado Copacabana S.A.S, and was created through different referenced human resources models, according to the needs of the sector and the expectations of the organization, obtaining a solid and complete model that works as an example for other companies in the same sector. This document defines Mercopa S.A.S.’s strategy. It was created from results of an analysis prepared for the company and a marketing research of nearby companies engaged in the same commercial activities. Furthermore, this project proposes a new organizational structure with job profiles, a human resources model with an emphasis on the application in a performance evaluation system, and an internal communication system. All of these practices are focused on human development and the company’s performance. Implementing this new strategy and human resources model in the company would not have any cost. However, it will be necessary to implement internal communication activities with the objective of making this new model understandable and applicable and making it part of the culture of the organization.
Keywords: modelo de gestión humana; planeación estratégica; desempeño; diseño organizacional; descripción de puestos de trabajo; proceso; human resources model; strategic planning; organizational structure; performance evaluation system; organizational design; jobs descriptions; process; Máster Universitario en Dirección y Gestión de Recursos Humanos